Urban Air Pollution Multivariate Analysis and Effect on Respiratory Morbidity in Industrial Regions - Mahmood , Irfan W. (American Journal of Biodiversity, 2026)
The purpose of the research was to evaluate the effects of urban air pollution on respiratory morbidity in the industrial district of Kirkuk city, which has high industrial activity. The study population consisted of 150 participants, with an age range of 18-65 years, and the majority were male (80%). Data were gathered in the form of environmental measurements of air pollutants, and health questionnaires, medical record reviews and pulmonary function tests. The findings revealed that the concentration of air pollutants was significantly high, with PM2.5 and PM10 levels exceeding the recommended limit, indicating a high environmental exposure. Respiratory diseases were also high in the study, with 48% having chronic respiratory symptoms, 38% had dyspnea, 29.3% had chronic bronchitis, and 25.3% had asthma.The statistical test showed that there is a significant correlation between high exposure to particulate matter and high risk of asthma (p < 0.01). Pulmonary function tests showed that there was a significant decline in FEV1 and FVC in those people who were subjected to high pollution levels. The multivariate logistic regression analysis established that PM2.5 exposure, smoking and industrial work are independent risk factors for high respiratory morbidity. The research concludes that respiratory health is under a severe threat from air pollution in industrial zones, and the environmental and health situation will need immediate intervention to minimize exposure and alleviate the disease burden caused by it.